Riding the waves of culture : understanding diversity in global business - Trompenaars, Fons; Hampden-Turner, Charles (Business professional collection, 2021)
"The bestselling guide to leading effectively in an increasingly global business environment-updated to address radical changes in politics, society, economics, and technology Today's geopolitical landscape has evolved dramatically, with major impacts on relationships among countries that do business together. As a business leader, your concerns are no longer simply about being aware of cultural differences and preventing embarrassments. Now, you must tread more lightly than ever, be even more attuned to cultural differences, and leverage cultural differences for maximum competitive advantage. Retaining its in-depth exploration of underlying cultural frameworks that have made it a business classic, Riding the Waves of Culture, Fourth Edition provides new, evidence-based information and insights on critical business matters, including: How to enhance and improve chances of success in M&A deals by expertly handling corporate and cultural differences Ways of improving and handling competencies, dilemmas, servant leadership, innovation, and remote-team effectiveness in an increasingly diverse business world New analyses of changes over the past 25 years that are moving the world closer to a single "global village" Renowned experts in their field, the authors also include new chapters and updates on the meaning of culture, assessing cultural competence, change management, assessing organization culture, and diversity and ethnicity. The most thoroughly researched and highly respected resource of its kind, Riding the Waves of Culture does more than help you stay afloat in today's diverse work environment; it provides the knowledge you need to seize the advantage and compete for the long run"--